“I was afraid, because I was naked”: Ethical literary criticism, the fall of Adam and Eve and moral teaching - Shilong Tao; Xi Chen (Heliyon, 2023)
This article explores the moral teachings in the fall of Adam and Eve (Gen 2:4–3:24) from the perspective of ethical literary criticism. According to the theory of three stages in human civilization—natural, ethical and scientific selection, the fall of Adam and Eve represents the historical process of human civilization going from natural selection to ethical selection. It is ethical selection that enables Adam and Eve to have ethical consciousness and distinguish themselves from animals, which provides ideas for the birth and growth of humans and highlights the function of “moral teaching and learning” in children's education. Besides, the so-called original sin is the animal factor remained in human beings after natural selection, which can bring about different ethical predicaments of “to be or not to be” and lead to making wrong ethical choices. The fall of Adam and Eve indicates that human beings are born with Sphinx factor—human factor and animal factor and integrate into the secular life and religious activity with divine factor. Once the animal factor of an individual is out of control, breaking the ethical taboo and violating the moral order or religious rule without exerting the power of human factor or divine factor, there will inevitably be punishments and tragedies. The fall of Adam and Eve is such an ethical tragedy, which purifies primitive desires and evokes moral emotions through pity and fear to uphold the morality in society and the authority in religion.